Sol–gel synthesis of nanoparticles of gamma alumina and their application in defluoridation of water - Singh I.B.; Gupta A.; Dubey S.; Shafeeq M.; Banerjee P.; Sinha A.S.K. (My University, 2025)
Abstract: Water solvent-based sol–gel process was employed in the synthesis of nanoparticles of gamma alumina (NPGA) which were used for the removal of fluoride from water of neutral pH. Different techniques like thermogravimetric analysis, Fourier transform infrared spectroscopy, X-ray diffraction, and field emission scanning electron microscopy were employed for the characterization of the synthesized particles. Batch adsorption studies were performed for the optimization of contact time and adsorbent doses to obtain maximum fluoride removal and understanding of the adsorption kinetics and mechanism. The maximum adsorption capacity of NPGA for fluoride removal was estimated to be nearly 14 mg/g at room temperature (30 °C) which is better than fluoride removal reported by earlier using of commercial-grade NPGA. Adsorption kinetics measurement indicated that Langmuir equilibrium model is found to be more suitable for describing the fluoride adsorption mechanism. Graphical Abstract: [Figure not available: see fulltext.] © 2015, Springer Science+Business Media New York.